2018
DOI: 10.3390/met8100825
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural Characterization of the Anisotropy and Cyclic Deformation Behavior of Selective Laser Melted AlSi10Mg Structures

Abstract: The laser-based fusion of metallic powder allows construction of components with arbitrary complexity. In selective laser melting, the rapid cooling of melt pools in the direction of the component building causes significant anisotropy of the microstructure and properties. The objective of this work is to investigate the influence of build anisotropy on the microstructure and mechanical properties in selective laser melted AlSi10Mg. The alloy is comprehensively used in the automotive industry and has been one … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(14 citation statements)
references
References 30 publications
1
13
0
Order By: Relevance
“…The issue of Young's modulus is more challenging to understand for aluminium alloys since these materials are almost elastically isotropic, so that the directional dependence of stiffness cannot be explained by texture variation. However, it should be noted that, similarly to our results, it has been shown that Young's modulus varies significantly within the range of 63-72 GPa for SLM 3D-printed AlSi 10 Mg alloy [31].…”
Section: Tionsupporting
confidence: 90%
See 1 more Smart Citation
“…The issue of Young's modulus is more challenging to understand for aluminium alloys since these materials are almost elastically isotropic, so that the directional dependence of stiffness cannot be explained by texture variation. However, it should be noted that, similarly to our results, it has been shown that Young's modulus varies significantly within the range of 63-72 GPa for SLM 3D-printed AlSi 10 Mg alloy [31].…”
Section: Tionsupporting
confidence: 90%
“…[28] and Tang M. [29] investigated an AlSi 10 Mg alloy and achieved the same results as in our study; namely, samples manufactured in the vertical direction (Z-X) showed higher values of ultimate tensile strength than specimens built in the horizontal direction (X-Y). However, there are other studies where samples printed with equal conditions and composition demonstrated the inverse relation [30,31]. Moreover, this stochastic behaviour of mechanical characteristics was found during tensile tests of samples with other alloy compositions such as AlSi 10 , A356 (AlSi 7 Mg 0.3 ) and A357 (AlSi 7 Mg 0.7 ) [27].…”
Section: Tionmentioning
confidence: 87%
“…The anisotropy in the SLMed parts is usually caused by the different solidification rates in different directions, and heat conductivity in the building direction (z-axis) is typically faster than that in the other two spatial directions (x-and y-axes) due to the high-heat transfer efficiency of the pre-deposited metals. [121][122][123] The microstructural anisotropy in the SLMed parts usually leads to anisotropic mechanical properties [124][125][126] and corrosion behaviours. 127,128 For the mechanical properties, there was a larger elongation along the building direction than in the other two spatial directions due to the grain growth mainly occurring along the building direction, such as for stainless steels and CoCrW alloys.…”
Section: Anisotropymentioning
confidence: 99%
“…15 A possible nondestructive test method to identify and characterize the process-induced porosity is the use of Xray computed tomography (CT). The method is widely used for different AM materials such as aluminum [16][17][18] and titanium alloys 19,20 for density measurements and characterization of pores and cracks. However, steels are challenging for X-ray applications due to their high density, high absorption coefficient, and the effect of beam hardening, causing artifacts and noise in the CT data.…”
Section: Introductionmentioning
confidence: 99%